Promoter Variation in the DC-SIGN–Encoding Gene CD209 Is Associated with Tuberculosis - Luis B. Barreiro; Olivier Neyrolles; Chantal Babb de Villiers; Ludovic Tailleux; Hélène Quach; Ken McElreavey; Paul D. van Helden; Eileen G. Hoal; Brigitte Gicquel; Lluı́s Quintana-Murci (2005)
Background Tuberculosis, which is caused by Mycobacterium tuberculosis, remains one of the leading causes of mortality worldwide. The C-type lectin DC-SIGN is known to be the major M. tuberculosis receptor on human dendritic cells. We reasoned that if DC-SIGN interacts with M. tuberculosis, as well as with other pathogens, variation in this gene might have a broad range of influence in the pathogenesis of a number of infectious diseases, including tuberculosis. Methods and Findings We tested whether polymorphisms in CD209, the gene encoding DC-SIGN, are associated with susceptibility to tuberculosis through sequencing and genotyping analyses in a South African cohort. After exclusion of significant population stratification in our cohort, we observed an association between two CD209 promoter variants (−871G and −336A) and decreased risk of developing tuberculosis. By looking at the geographical distribution of these variants, we observed that their allelic combination is mainly confined to Eurasian populations. Conclusions Our observations suggest that the two −871G and −336A variants confer protection against tuberculosis. In addition, the geographic distribution of these two alleles, together with their phylogenetic status, suggest that they may have increased in frequency in non-African populations as a result of host genetic adaptation to a longer history of exposure to tuberculosis. Further characterization of the biological consequences of DC-SIGN variation in tuberculosis will be crucial to better appreciate the role of this lectin in interactions between the host immune system and the tubercle bacillus as well as other pathogens.